ROLE OF FIBRIN GLUE FOR BETTER SUCCESS RATE IN MYRINGOPLASTY - Aslam, Sohail; Asghar, Adnan; Bukhari, Syed Muhammad Asad Shabbir; Akhtar, Sunarays; Mumtaz, Hamza; Waseem, Muhammad Fahad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To see graft uptake success rate in platelet rich fibrin aided underlay myringoplasties using temporalis fascia graft compared to conventional underlay myringoplasties.Study Design: Double blind randomized controlled trial study.Place and Duration of Study: ENT department, Pakistan Naval Ship Shifa Hospital, from Jan to Jun 2019.Methodology: Sixty cases with dry central tympanic membrane perforations were recruited. The patients suffering from sensori-neural hearing loss and co-morbidities like diabetes were excluded. The sampling technique was probability simple random. Patients were divided into two groups by lottery method. Statistical analysis was performed by using SPSS. The chi square test was applied to calculate p-value.Results: Out of total 60 patients 38 were males and 22 were females. Study group’s (Fibrin) mean age was 31.77 ± 12.43 years and Control group’s mean age was 27.53 ± 11.41 years. All the patients in platelet rich fibrin group had successful graft uptake at 2 months follow-up. In control group with conventional technique 23 out of 30 patients had successful graft uptake and rest 7 patients had different issues leading to graft rejection.Conclusion: In under lay myringoplasty procedure, application of platelet rich fibrin on temporalis fascia graft edge and perforation edges has significantly improved the successful uptake rate of graft.